The Education of a Child up to Seven Years of Age. The Polish Perspective - Sadowska, Katarzyna; Kuszak, Kinga (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2025)
Celem opracowania jest ukazanie historycznych oraz społecznych kontekstów edukacji dziecka do lat siedmiu w obliczu najważniejszych czynników kształtowania się polskiej tradycji w omawianym obszarze. Autorki przyjmują, że szeroko ujmowana, zmieniająca się rzeczywistość historyczna, społeczna, geograficzna, polityczna i ekonomiczna wyznacza zmiany w myśleniu o edukacji, wpływa na ideologie edukacyjne oraz na formułowane cele edukacji na poziomie kraju. W monografii podjęto refleksję nad trzema głównymi problemami: dziecko jako podmiot polskiej edukacji (w tym np. sposoby osiągania samodzielności przez dziecko, znaczenie wsparcia ze strony nauczycieli w związku z wyzwaniami współczesnego świata); edukacja dziecka w polskim żłobku (w tym m.in. zakres tematyczny pojęcia „wczesnodziecięca edukacja”, wyniki badań focusowych zrealizowanych z opiekunkami żłobków z terenu Wielkopolski); edukacja dziecka w polskim przedszkolu (w tym np. analiza obowiązującej w Polsce podstawy programowej wychowania przedszkolnego czy zmiany w obszarze znaczenia, roli, zadań przedszkoli w Polsce). The Education of a Child up to Seven Years of Age. The Polish Perspective jest pierwszym opracowaniem w języku angielskim, które analizuje kształtowanie się tradycji polskiej edukacji dziecka do lat siedmiu. The book aims to present the historical and social contexts of education of children up to the age of seven in the face of the most important factors shaping the Polish tradition in this field. The authors assume that the changing historical, social, geographical, political and economic reality, understood in the broad sense, determines changes in thinking about education, influencing educational ideologies and education goals formulated at the national level. The monograph reflects on three main problems: the child as a subject of Polish education (including ways in which the child achieves independence, and the importance of teacher support in relation to the challenges of the modern world); the education of the child in the Polish nursery school (including the scope of the term ‘early childhood education’, and the results of focus studies conducted with nursery school caregivers from the Wielkopolska region); education in the Polish kindergarten (including an analysis of the binding Polish core curriculum for kindergarten education or changes in the meaning, role, tasks of kindergartens in Poland). The Education of a Child up to Seven Years of Age. The Polish Perspective is the first study in English to analyse the formation of the Polish tradition of educating a child up to the age of seven.
Keywords: żłobek; edukacja dzieci; konteksty historyczne; konteksty polskie; nauczyciele dzieci; przedszkole